Perlindungan Hukum Terhadap Anak Korban Kekerasan: Studi Kasus Putusan Pengadilan Negeri Gunungsitoli - Hia, Hipotesa; Mulyadi, Mahmud; Siregar, Taufik (Universitas Medan Area, 2019)
The purpose and benefits of this research are to find out violence against children in Gunungsitoli court, to find out legal efforts in protecting children against child abuse, to find out the inhibiting factors in protecting children in Gunungsitoli District Court. The benefit is to provide input to the Gunungsitoli district court regarding legal protection for victims of violence. This research is analytical descriptive, which means describing the facts studied and the relationship with the legislation, theories, and opinions of legal experts. Conclusions and advice on legal protection according to positive law Indonesia never guarantees the fulfillment of children's rights, especially the rights of children who receive an education. Hereby the state's legal obligations in child protection will depend on the positive laws that exist in the country, so that child protection can be adequate in the application of children, and efforts to protect children need support from the government and the community in terms of effective and comprehensive child comfort. In this case, given the increase in violence against children every year, it is necessary to have the legal protection that must be taken seriously by the government, the community and other non-governmental organizations.